POLA PENGGUNAAN OBAT ANTIRETROVIRAL (ARV) PADA RESEP PASIEN RAWAT JALAN DARI KLINIK HIV/AIDS SALAH SATU RUMAH SAKIT SWASTA DI KOTA BANDUNG - Anggriani, Ani; Lisni, Ida; Liku, Olga Susana (APDFI (Asosiasi Pendidikan Diploma Farmasi Indonesia), 2019)
ABSTRACT The Human Immunodeficiency Virus (HIV) continues to be a major global public health issue, which targets the human immune system. The using of ARVs in the treatment of HIV / AIDS increased life expectancy for PLHIV (People With HIV / AIDS). This study aims to determine the description of the using of ARV drugs in outpatients of the HIV / AIDS Clinic and assessed their suitability with established treatment standards. This research was carried out in a descriptive non-experimental manner, with data collection carried out retrospectively, used patient prescription data from April to December 2017. The results of quantitative studies showed 87% were male patients, and the largest age group was 20-29 years (39%) . Class of antiretroviral drugs used were Nucleoside / Nucleotide Reverse Transcriptase Inhibitors (NRTIs), Non-Nucleoside Reverse Transcriptase Inhibitors (NNRTIs), and Protease Inhibitors (PI), with a combination of antiretroviral drugs most was the combination of first-line tenofovir + lamivudine + efavirenz (69%) while the second-line drug zidovudine + lamivudine + lopinavir / ritonavir was 1%. The most commonly used comorbid drug was cotrimoxazole. For qualitative data, the accuracy of combination and dose of ARV drugs was 100% in accordance with Permenkes No. 87/ 2014, with 79% of patients adhered to antiretroviral treatment every month. The potential for most ARV drug interactions with other drugs for the moderate category was zidovudin + cotrimoxazole (11%) which occured pharmacokinetically by decreasing renal clearance of zidovudine and glucuronide metabolites. In conclusion, the pattern of used of ARV drugs had met the standard of Permenkes No.87/2014, with the most used were the first line combination of tenofovir + lamivudine + efavirenz.